2009
DOI: 10.1063/1.3095561
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniformity for rotated beam illumination in directly driven heavy-ion fusion

Abstract: A bstractA key issue in heavy-ion beam inertial confinement fusion is target interaction, especially implosion symmetry. In this paper the 2D beam irradiation nonuniformity on the surface of a spherical target is studied. This is a first step to studies of 3D dynamical effects on target implosion. So far non-rotated beams have been studied. Because normal incidence may increase Rayleigh-Taylor instabilities, it has been suggested to rotate beams (to increase average uniformity) and hit the target tangentially.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In the time averaged energy deposition onto a spherical direct drive target, the averaged illumination nonuniformity was small, for example, less than a few percent [6]. However, it was found that the initial imprint of the rotating axis HIBs is serious and introduces a large illumination nonuniformity.…”
Section: Spiraling Heavy Ion Beam Illumination Uniformitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the time averaged energy deposition onto a spherical direct drive target, the averaged illumination nonuniformity was small, for example, less than a few percent [6]. However, it was found that the initial imprint of the rotating axis HIBs is serious and introduces a large illumination nonuniformity.…”
Section: Spiraling Heavy Ion Beam Illumination Uniformitymentioning
confidence: 99%
“…So far the wobbling HIBs illumination has been considered by the time averaged illumination [3][4][5][6]. In the time averaged energy deposition onto a spherical direct drive target, the averaged illumination nonuniformity was small, for example, less than a few percent [6].…”
Section: Spiraling Heavy Ion Beam Illumination Uniformitymentioning
confidence: 99%
See 3 more Smart Citations